Factors Contributing to the Utilization of Traditional Medicine in the Treatment of Ear, Nose, and Throat Conditions - Agyemang, Cecilia Opoku; Opoku, Oscar Agyemang (Journal of Health Sciences and Medical Development, 2025)
The rate of the use of traditional medicine continues to grow worldwide and is the preferred treatment in especially rural communities in developing countries. This study assessed the factors contributing to the utilization of traditional medicine in the treatment of Ear, Nose, and Throat (ENT) conditions in Kumasi. This quantitative study used a descriptive survey study design to answer the research questions. Convenience sampling technique was used in sampling 166 respondents for the study using Yamen’s formula. A questionnaire was developed to gather information under each objective. Data was analyzed using Statistical Package for Social Science Software to present descriptive analysis. Results from the study showed majority of the respondents believed that cultural beliefs influenced the usage of traditional medicine in the treatment of ENT conditions as more than half of the respondents; 141 (84.9%) responded yes to the statement, ‘Traditional medicine is associated with religious and spiritual underpinnings’. Also, cost, spirituality, social relationships, and health workers' interpersonal relationships among others affected the usage of traditional medicine among the respondents. It was therefore concluded that cultural beliefs are a very significant factor that contributes to the usage of traditional medicine in the treatment of ENT conditions. It is therefore recommended that the Ministry of Health in collaboration with the various health directorates in Kumasi should plan and organize a public awareness campaign program to educate the general population about the potential benefits and risks of traditional medicine.